Magnetization in AIIIBV semiconductor heterostructures with the depletion layer of manganese - Charikova, T.; Okulov, V.; Gubkin, A.; Lugovikh, A.; Moiseev, K.; Nevedomsky, V.; Kudriavtsev, Yu.; Gallardo, S.; Lopez, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The magnetic moment and magnetization in GaAs/Ga0.84In0.16As/GaAs heterostructures with Mn deluted in GaAs cover layers and with atomically controlled Mn δ-layer thicknesses near GaInAs-quantum well (~3 nm) in temperature range T = 1.8–300 K in magnetic field up to 50 kOe have been investigated. The mass mag-netization all of the samples of GaAs/Ga0.84In0.16As/GaAs with Mn increases with the increasing of the magnetic field that pointed out on the presence of low-dimensional ferromagnetism in the manganese depletion layer of GaAs based structures. It has been estimated the manganese content threshold at which the ferromagnetic ordering was found.